The diagnostic analysis of the planet bearing faults using the torsional vibration signal. (1st December 2019) - Xue, Song; Howard, Ian; Wang, Congsi; Bao, Hong; Lian, Peiyuan; Chen, Gaige; Wang, Yan; Yan, Yuefei
Highlights: The planetary gear mathematical model with detailed planet bearing dynamics was developed. The planet bearing stiffness was calculated by the Hertzian contact theory. The planet bearing faults were modelled and incorporated into the planetary gear model. A modified signal processing method were used to enhance the instantaneous angular speed. The IAS signal was found to be an effective tool for the planet bearing monitoring. Abstract: This paper aims to investigate the effectiveness of using the torsional vibration signal as a diagnostic tool for planet bearing fault detection. The inner race of the planet bearing is connected to the planet carrier and its outer race is connected to the planet gear bore hole. When moving, the planet bearing not only spins around the planet gear axis, but also revolves about the sun gear axis. This rotating mechanism poses a challenge for the condition monitoring of the planet bearing because of the variant vibration transfer paths. The transducer mounted on the carrier arm measuring the torsional vibration is theoretically free from this modulation effect and it is used in this research to extract the diagnostic information from the torsional vibration. A 34 degrees of freedom planetary gear lumped-parameter model with detailed planet bearing model was developed to obtain the dynamic response. The planet bearing was modelled by 5 degrees of freedom, with 2 degrees of freedom from the outer race, 2 degrees of freedom from the inner race and one degree of freedom from the sprung-mass. The variations of the sun-planet and ring-planet mesh stiffnesses were evaluated by the finite element method and the variation of the planet bearing stiffness was evaluated by the Hertzian contact theory. The localized faults on the planet bearing inner race, outer race and the rolling element were created mathematically and then these faults were incorporated into the planetary gear model to obtain the faulted vibration signal. The linear prediction method and the minimum entropy deconvolution method were used to enhance the planet bearing signal and then the amplitude demodulation results were analysed. It was found that the carrier arm instantaneous angular speed was an effective alternative approach for planet gear condition monitoring.